Experimental economics and culture - Gunnthorsdottir, Anna; Norton, Douglas A., 1984- (Research in experimental economics ;, 2018)
Culture has been referred to as a shared frame, the lens through which group members make sense of the world. It has been robustly linked to economic outcomes on the macro level and is also directly linked to decision-making: in recent years, experimental and behavioral economists have found evidence that culture impacts behavior in games and impacts value orientation, trust, fairness, cooperation and enforcement. Culture research in experimental economics is still in its early stages and part of the challenge is methodological and conceptual: how to measure culture and how to define the level at which individuals share a culture. In the coming years, this research will help delineate where the results from our current experiments apply. For example, do current results speak specifically to WEIRD (Western Educated Industrialized Rich Democracies) societies? Do they say something more fundamental about human nature across time, experience, and geography? With increasing migration and globalization, subject pools may become more culturally diverse and cultural questions therefore increasingly important for experimentalists. The contributions in this volume are both conceptual and experimental. The earlier chapters discuss new approaches to the measurement of culture and how to conceptualize and define values and beliefs and the groups that share them. The latter experimental chapters contribute to the growing body of literature that documents cultural differences in social and economic behavior.